High-Resolution Imaging of a Single Gliding Protofilament of Tubulins by HS-AFM - Jakia Jannat Keya (Nature Portfolio, 2017)
Abstract In vitro gliding assay of microtubules (MTs) on kinesins has provided us with valuable biophysical and chemo-mechanical insights of this biomolecular motor system. Visualization of MTs in an in vitro gliding assay has been mainly dependent on optical microscopes, limited resolution of which often render them insufficient sources of desired information. In this work, using high speed atomic force microscopy (HS-AFM), which allows imaging with higher resolution, we monitored MTs and protofilaments (PFs) of tubulins while gliding on kinesins. Moreover, under the HS-AFM, we also observed splitting of gliding MTs into single PFs at their leading ends. The split single PFs interacted with kinesins and exhibited translational motion, but with a slower velocity than the MTs. Our investigation at the molecular level, using the HS-AFM, would provide new insights to the mechanics of MTs in dynamic systems and their interaction with motor proteins.